Hungarian Monitoring, 11 April 1989 . [Magyar rádiófigyelő], 1989. április 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Warsaw Pact foreign ministerial committee session begins - Gherasimov's press conference on the Georgian situation - Polish Catholic church counter-offensive on abortion - Signs indicate that West Germany does not want deterioration in relations with Romania Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) rural reform circles - Debates about proposed car use fee - Conversation with three representatives who have left the Party: László Lengyel, Zoltán Bíró and Mihály Bihari - There will be May 1 rally held in Budapest - Democratic Trade Union of Academics against the Gabčíkovo-Nagymaros investment project - Interview with Sándor Csoóri - Editors of "Tiszatáj" magazine banned on July 1, 1986 are morally rehabilitated Economy: - Estimates indicate that prices dispute between Csepel Car Factory and Ikarusz caused HUF 0.5 million damage - Interview with deputy minister Zsigmond Járai: no shares law, no stock exchange law, although the stock exchange already exists - Hungarian People's Party planned agricultural reform Külpolitika - Megkezdődött a VSZ külügyminiszteri bizottságának ülése - Geraszimov sajtó értekezlete a grúziai helyzetről - Ellentámadásba lendült a lengyel katolikus egyház az abortusz ügyben - A jelek szerint az NSZK nem akarja tovább rontani kapcsolatait Romániával Belpolitika: - Az MSZMP vidéki reformkörei - Viták a bevezetendő autóhasználati díj körül - Beszélgetés a pártból kilépett három képviselővel, Lengyel Lászlóval, Bíró Zoltánnal és Bihari Mihállyal - Mégis lesz felvonulás május 1-én Budapesten - A TDDSZ a bős-nagymarosi beruházás ellen - Interjú Csoóri Sándorral - Erkölcsileg is rehabilitálták az 1986 július 1-én betiltott TISZATÁJ szerkesztőségét Gazdaság: - Becslések szerint fél milliárd forint kárt okozott a Csepel Autógyár és az IKARUSZ árvitája - Hiányzik egy értékpapír törvény, hiányzik egy tőzsde törvény, de tőzsde már van. Interjú Járai Zsigmond miniszterhelyettessel - A Magyar Néppárt agrárreform tervezete